Application of Geographic Information Technologies for Logistic Centers Planning – Kocaeli Example - Arzu Erener; Mustafa Kurt (Journal of Transportation and Logistics)
Establishing the most appropriate location of the facility in terms of logistics distribution network and customers can be quite critical. Potential suitability investigation of the region to set up an appropriate logistics geographical area center would be useful to be determined from multiple criterea. In geographic information systems (GIS), spatial analysis which consider multiple criteria are called multi-criteria decision analysis (MCDA). The aim of this study is to evaluate planning performance of GIS to determine logistics centers. This study was conducted to analyze the most suitable place for establishing new logistic park according to specified five criteria. The criteria which taken to account in practice have identified as: production areas, residential areas, leisure areas, transit transport network and slope map. Kocaeli district was selected as study of area. After all to the direction of selected criteria and given weights; close to the industrial areas, away from the residential areas, low slope areas, quit close to transit and port areas were identified as potential logistics park areas and GIS was found rapid and objective to produce suitable potential logistic areas.